CLINICAL OUTCOMES OF EARLY RESUSCITATION IN ISCHEMIC STROKE - 1Sayfudinov Abbos Alisher oglu, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Ischemic stroke, a leading cause of global mortality and long-term disability, represents a neurological emergency where time is brain. The efficacy of all therapeutic interventions is critically dependent on the speed and quality of initial medical care, extending beyond specific reperfusion therapies. This article provides a comprehensive analysis of the clinical outcomes associated with early, systematic resuscitation and management in the hyperacute phase of ischemic stroke. It examines the impact of optimized prehospital and emergency department care, focusing on airway and breathing management, hemodynamic optimization (permissive hypertension vs. aggressive lowering), glycemic and temperature control, and the rapid identification of large vessel occlusion (LVO). The review synthesizes evidence demonstrating that structured early resuscitation, encapsulated in the "Stroke Chain of Survival" and "Code Stroke" protocols, directly improves eligibility for and outcomes of thrombolysis and mechanical thrombectomy. Key findings indicate that every minute of delay in reperfusion results in the loss of 1.9 million neurons, making pre- and in-hospital processes pivotal. The conclusion underscores that early resuscitation is not merely supportive but a fundamental, active treatment component that preserves the ischemic penumbra, reduces infarct growth, and significantly enhances functional recovery, as measured by the modified Rankin Scale (mRS) at 90 days.